ANALISIS PELAKSANAAN PEMBELAJARAN DARING PADA MATA PELAJARAN IPS SELAMA MASA PANDEMI COVID-19 DI KELAS VIII SMP NEGERI 1 TOMA - Alfrida Yurni Mardayanti Loi (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2022)
The research method used is a qualitative research method with a case study approach. Data collection techniques using observation, interviews and documentation. The data analysis technique uses data reduction stages, data display, conclusions and verification, final conclusions. The validity of the data uses credibility, transferability, dependability, confirmability. The results of this study indicate that online learning activities at SMP Negeri 1 Toma are carried out through WhatsApp groups, where subject teachers distribute material to students through groups and then distribute assignments to students also through groups. For assignments given to teachers, students send these assignments to subject teachers via personal WhatsApp instead of through class groups. The shortcomings experienced by SMP Negeri 1 Toma in the implementation of online learning are the absence of the required electronic devices and their accessories such as cellphones, internet packages, plus a network that is sometimes not smooth. The advantage of implementing online learning activities at SMP Negeri 1 Toma is that there is understanding from the school and from the subject teachers through efforts to hold face-to-face meetings. The suggestions that researchers can convey are that it is hoped that schools will facilitate tools used in online learning such as computers and wifi networks.